Biological Activities and Potential Applications of Phytotoxins (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint focuses on the isolation and characterization of some phytotoxins and the evaluation of their biological activities for potential application in different fields. Plants and microbes are able to produce several specialized (secondary) metabolites belonging to different classes of natural compounds. Among them, phytotoxins are substances that are poisonous or toxic to plants. They seem to play an important role in plant–pathogen interactions when produced by phytopathogenic fungi or bacteria, while plant-produced phytotoxins—including allelochemicals—seem to be involved in plant–plant interactions. Thus, the determination of their chemical structure and their identification are fundamental for chemical ecology and for understanding their function. However, most of these compounds have already shown other interesting biological activities and potential applications in fields such as agriculture or medicine. In fact, some phytotoxins have already been proposed for the development of biopesticides, cosmetics, and drugs.